The mediating effect of stigma between self-perceived burden and loneliness in stroke patients - Fan, Wenfeng; Ma, Ke ke; Yang, Cai xia; Guo, Yuan li (Frontiers in Psychiatry, 2023)
Introduction Stroke patients may experience reduced socialization and feelings of isolation due to post-stroke sequelae such as impaired motor function and cognitive deficits. Factors associated with loneliness need to be explored to develop targeted interventions. However, little is known about the impact of self-perceived burden and illness stigma on loneliness in this population.The aim of this study was to explore the mediating effect of stigma on self-perceived burden and loneliness in stroke patients Design:A cross-sectional study. Methods The cluster random sampling method was adopted to select 1028 stroke patients from the neurology department of third-grade A hospitals and second-grade A hospitals in 5 cities of Henan Province from May 2022 to August 2022. A general data questionnaire, self-feeling scale, stroke stigma scale, and loneliness scale were used to investigate. The structural equation model was used to analyze the mediating effect of stigma between perceived burden and stigma. Results The loneliness of stroke patients was positively correlated with perceived burden and stigma. The results of the mediation analysis showed that stigma played a complete mediating role between perceived burden and loneliness. Conclusion The results of the study revealed the relationship between self-perceived burden, stigma, and loneliness in stroke patients. Sickness stigma mediated the relationship between self-perceived burden and loneliness in this population. Relevance to clinical practice:This study reminds healthcare providers to be aware of patients' self-perceived burden and stigma, which can assist in developing effective interventions to improve stroke patients' sense of loneliness in clinical practice.